The History of Policing in the Maritime Provinces: Themes and Prospects - Marquis, Greg (Urban History Review / Revue d'histoire urbaine, 1990)
This article is an overview of the development of policing in the Maritime provinces and a commentary on the potential of such research to augment our understanding of the urban past. Police records, it is argued, are important social indicators which can reveal more than crime or fear of crime in a community. The article discusses police records and statistics; 19th century urban policing; early 20th century themes such as technology and Prohibition; the role of the Provincial police and Royal Canadian Mounted Police in the region; police and labour and police organizations. It concludes that researchers should be sensitive to both 'hard' and 'soft' police policies and pay special attention to the police service role.